2019
DOI: 10.1002/cam4.2711
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics based on 18F‐FDG PET/CT could differentiate breast carcinoma from breast lymphoma using machine‐learning approach: A preliminary study

Abstract: Purpose: Our study assessed the ability 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) radiomics to differentiate breast carcinoma from breast lymphoma using machine-learning approach. Methods: Sixty-five breast nodules from 44 patients diagnosed as breast carcinoma or breast lymphoma were included. Standardized uptake value (SUV) and radiomic features from CT and PET images were extracted using local image features extraction software. Six discriminative models inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
1
30
0
2
Order By: Relevance
“…We evaluated 20 publications on breast cancer [ 59 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 ], all of them using FDG as the radiotracer. The average number of patients was 118 (median = 81, range, 34–435).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated 20 publications on breast cancer [ 59 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 ], all of them using FDG as the radiotracer. The average number of patients was 118 (median = 81, range, 34–435).…”
Section: Resultsmentioning
confidence: 99%
“…In one of the most relevant works assessing diagnosis, Ou et al [ 194 ] evaluated the ability of PET and CT radiomics to differentiate breast carcinoma from breast lymphoma using a machine-learning approach. They validated their findings in a separate subsample of the cohort, obtaining an AUC of 0.81 for PET radiomics, which outperformed CT radiomics.…”
Section: Resultsmentioning
confidence: 99%
“…To date, studies that have analyzed radiomic features based on [ 18 F]FDG-PET/CT in patients with breast cancer have focused on building models to predict pathological complete response to neoadjuvant chemotherapy or to differentiate breast carcinoma from breast lymphoma [ 20 , 22 , 65 ]. Antunovic et al reported AUCs of 0.70–0.73 across all predictive models [ 22 ]; Li et al reported AUCs of 0.72 and 0.73, respectively, without and with patient age incorporated [ 20 ]; and Ou et al reported AUCs of 0.81 and 0.76 for PET and CT models, respectively [ 65 ]. Huang et al [ 66 ] reported mean AUCs of 0.75 and 0.68 for one-year and two-year recurrence-free survival, respectively, from using PET/MRI-based models.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PET imaging, the role of this functional technique has been explored in breast cancer mainly for prognostic/therapeutic purposes, particularly in the early prediction of the response to neoadjuvant chemotherapy [39][40][41]. In a recently published study, the usefulness of radiomics and ML applied to PET/CT to differentiate breast carcinoma from lymphoma was investigated in a small number of lesions (19 breast lymphoma and 25 breast cancer lesions) [42]. Different predictive models were built using combinations of clinical data, quantitative parameters (SUV), radiomics features ( rst and second order parameters extracted from both PET and CT images) and CT images.…”
Section: Discussionmentioning
confidence: 99%